Diseño y modelado de un sistema automático con redes de Petri para el control del factor de potencia - Varas Díaz, Renato Alejandro (2015)
This thesis is intended to create the design and modeling of a system Petri Net Control Power Factor in single phase systems, the design of the Petri net it is done using a software tool called VisualObjectNet, used to structure systems stochastic control using knowledge of Petri Nets need four basic elements that define the stochastic systems, these elements are the places, Arc, Transitions and Toquens, the same system is checked and run in Matlab is a mathematical tool used in topics or engineering topics while a test of practical use in the laboratory system, this thesis proposing a new system for power factor correction focused on the single phase systems.